2016
DOI: 10.1080/00952990.2016.1188934
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and drinking game participation among university students: the moderating role of drinking to cope

Abstract: Results demonstrated the influence of drinking to cope in the relationship of social anxiety with frequency of drinking game participation. Future work should examine the relationship with other indicators of drinking game activity. Intervention efforts addressing social anxiety and drinking should consider motives for drinking, as well as drinking patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…There has been recent growth in DGs research among university students outside the USA [3,4,9,18], although Australian research remains limited. However, further research designed to validate this measure with young adults in other parts of the globe where DGs are common is warranted.…”
Section: Motives For Playing Drinking Gamesmentioning
confidence: 99%
See 4 more Smart Citations
“…There has been recent growth in DGs research among university students outside the USA [3,4,9,18], although Australian research remains limited. However, further research designed to validate this measure with young adults in other parts of the globe where DGs are common is warranted.…”
Section: Motives For Playing Drinking Gamesmentioning
confidence: 99%
“…However, further research designed to validate this measure with young adults in other parts of the globe where DGs are common is warranted. More recently, a study of 227 student drinkers aged 18-24 years found that the majority (63%) played DGs at least 'some of the time' when consuming alcohol [3]. A 2007 study of 256 university student drinkers aged 18-25 years identified that 68% of Australian university students had played a DG in the prior 6 months [5].…”
Section: Motives For Playing Drinking Gamesmentioning
confidence: 99%
See 3 more Smart Citations